PENGARUH KETERBUKAAN DIRI (SELF DISCLOSURE) RELAWAN PENGAJAR DAN SISWA TERHADAP KEPERCAYAAN INTERPERSONAL DALAM MOTIVASI BELAJAR DI YAYASAN SWARA PEDULI CERIA - Nabila Adina Putri (2022)
Self-disclosure that is built will lead to a sense of interpersonal trust. Interpersonal trust will be the basis for the success of a motivation. This study aims to determine the positive effect of self-disclosure (self-disclosure) of teaching volunteers and students in the process of implementing teaching and learning in the Swara Peduli Foundation on interpersonal trust in learning motivation. Operational variables in this study consist of self-disclosure as the X variable and interpersonal trust as the Y variable. This study uses a quantitative method with the social penetration theory. The data collection technique was carried out using a survey method of distributing questionnaires to the object to be studied, namely 28 respondents. Sampling in this study used a saturated sample (census) because the number of respondents was less than 100 people. Based on the results of the coefficient of determination test and hypothesis testing, the results showed that there was a high positive influence on self-disclosure towards interpersonal trust, this can be seen from the calculation of the correlation value R = 0.795 and it is known that the R Square value is 0.632, it can be concluded that the magnitude of the influence has a value of 63.2%. The hypothesis which states that there is a positive effect of self-disclosure on interpersonal trust in learning, motivation at the Swara Peduli Foundation is acceptable.